Hospitality & events north : the corporate hospitality magazine for the Midlands, North of England, Scotland & North Wales.: the corporate hospitality magazine for the Midlands, North of England, Scotland & North Wales. Issue 96 Issue 96 (September 2023) - Unknown
No abstract available